Using cluster analysis in adult education - Gary J. Conti (Adult Education Research Conference, 1996)
Cluster analysis is a powerful multi variate tool available to adult educators for inductively identifying groups, which inherently exist in the data. Its power lies in its ability to examine the person in a holistic manner rather than as a set of unrelated variables. Once clusters are identified, other qualitative and quantitative techniques should be used to help name and describe the clusters.